Inhibition of NOX1 Mitigates Blood Pressure Increases in Elastin Insufficiency. Issue 3 (15th March 2021) - Troia, Angela; Knutsen, Russell H; Halabi, Carmen M; Malide, Daniela; Yu, Zu Xi; Wardlaw-Pickett, Amanda; Kronquist, Elise K; Tsang, Kit Man; Kovacs, Attila; Mecham, Robert P; Kozel, Beth A
Abstract: Elastin (ELN) insufficiency leads to the cardiovascular hallmarks of the contiguous gene deletion disorder, Williams–Beuren syndrome, including hypertension and vascular stiffness. Previous studies showed that Williams–Beuren syndrome deletions, which extended to include the NCF1 gene, were associated with lower blood pressure (BP) and reduced vascular stiffness. NCF1 encodes for p47phox, the regulatory component of the NOX1 NADPH oxidase complex that generates reactive oxygen species (ROS) in the vascular wall. Dihydroethidium and 8-hydroxyguanosine staining of mouse aortas confirmed that Eln heterozygotes ( Eln +/− ) had greater ROS levels than the wild-types ( Eln +/+ ), a finding that was negated in vessels cultured without hemodynamic stressors. To analyze the Nox effect on ELN insufficiency, we used both genetic and chemical manipulations. Both Ncf1 haploinsufficiency ( Ncf1 +/− ) and Nox1 insufficiency ( Nox1 −/y ) decreased oxidative stress and systolic BP in Eln +/− without modifying vascular structure. Chronic treatment with apocynin, a p47phox inhibitor, lowered systolic BP in Eln +/−, but had no impact on Eln +/+ controls. In vivo dosing with phenylephrine (PE) produced an augmented BP response in Eln +/− relative to Eln +/+, and genetic modifications or drug-based interventions that lower Nox1 expression reduced the hypercontractile response to PE in Eln +/− mice to Eln +/+ levels. These results indicate that the mechanical and structural differences caused by ELN insufficiency leading to oscillatory flow can perpetuate oxidative stress conditions, which are linked to hypertension, and that by lowering the Nox1-mediated capacity for vascular ROS production, BP differences can be normalized. :